Pernikahan Wanita Hamil Karena Zina (Married by Accident) dalam Persfektif Sosio Kultural Masyarakat Metro Utara (Studi Tentang Dampak dan Upaya Penanggulangannya) - Fatkul Mujib, M.H (Al Qadhi Journal of Islamic Family Law, 2019)
Abstract Marriage of pregnant women because of adultery is a legal matter as well as a social problem. Based on research on the reality of marriage of pregnant women due to adultery that occurs in Metro North District, the following matters can be concluded: Metro North people's perceptions of the legal provisions related to the marriage of pregnant women because adultery is largely influenced by the function of social institutions through religious leaders and community leaders, this has implications for the effectiveness and understanding of the public regarding formal law regarding the issue of pregnant marriage. Marriage of pregnant women due to adultery that occurs in Metro Utara Subdistrict as a social reality which is considered normal then constructs the sociological paradigm of the community of Metro Utara Subdistrict, which empirically describes the people's passivity towards the case of pregnant women due to adultery. Countermeasures for the issue of marriage of pregnant women due to adultery have been carried out by various parties in Metro Utara. These efforts include preventive, curative and repressive efforts. However, the existing efforts are still pragmatic and incidental.